2018
DOI: 10.2217/nnm-2017-0309
|View full text |Cite
|
Sign up to set email alerts
|

Silica Nanoparticles Actively Engage With Mesenchymal Stem Cells in Improving Acute Functional Cardiac Integration

Abstract: These findings provide strong evidence that SiO-NPs actively engage in mediating biological effects, ultimately resulting in augmented hMSC acute cardiac integration potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 57 publications
3
21
0
Order By: Relevance
“…MSCs can differentiate into cardiomyocytelike cells, integrate into host tissue, and enhance resident cell activity [138]. With the help of nano-biomaterials, MSCs have achieved better differentiation and functional integration for repairing myocardial infarction repair [139][140][141]. Transplanted MSCs can integrate into partially hepatectomized or toxicinjured liver for hepatic regeneration [142,143].…”
Section: Integration Of Differentiated Mscsmentioning
confidence: 99%
“…MSCs can differentiate into cardiomyocytelike cells, integrate into host tissue, and enhance resident cell activity [138]. With the help of nano-biomaterials, MSCs have achieved better differentiation and functional integration for repairing myocardial infarction repair [139][140][141]. Transplanted MSCs can integrate into partially hepatectomized or toxicinjured liver for hepatic regeneration [142,143].…”
Section: Integration Of Differentiated Mscsmentioning
confidence: 99%
“…Limited studies provided the vascular injury and dysfunction caused after SiNPs inhalation, probably associated with oxidative stress and inflammatory response [27]. In contrast, studies pointed out the good biological safety of SiNPs, which could improve the efficacy of cell therapy for myocardial infarction, and was considered the best candidate for stem cell therapy in cardiac tissue [28]. Owing to controversial results and to the lack of sufficient data to clearly identify the pro-atherogenic effects of SiNPs, we aim to study the long-term influence of SiNPs on the progression of atherosclerotic plaque by using ApoE-knockout (ApoE −/− ) mice fed a Western diet and conduct in vitro experiments for mechanism research.…”
Section: Introductionmentioning
confidence: 99%
“…NPs may be a potential approach to address this problem. It has been demonstrated that NPs can enhance stem cell retention by providing a cardiac-specific extracellular matrix (ECM) environment (include impacts some signal pathway), affecting the focal adhesion complex of myocardial MSCs (Bejleri et al, 2018), promoting the interactions with cardiomyocytes and affecting lysosomal function in ischemic environments (Popara et al, 2018). Magnetic NPs seem to resolve this accumulation to some extent.…”
Section: Nps Enhance Stem Cell Retention After Transplantationmentioning
confidence: 99%